Caracterización de ácaros productores de sarna (Demodex spp. y Sarcoptes spp.) en caninos en dos albergues en la ciudad de Popayán (2022)
Dogs can suffer from various dermatological diseases, among which are mange, this disease, can be highly contagious among them as is sarcoptic mange or, on the other hand, be in the same way immensely contagious to humans due to its zoonotic character, in the same way, scabies can be an immune-mediated factor as it is in the case of demodectic mange. The objective of this study is to characterize scabies-producing mites (demodex spp. and sarcoptes spp.) in canines in two hostels in the city of Popayán. In this work, a descriptive, cross-sectional study was carried out where skin scrapings of 27 canines with representative scabies lesions were carried out in two shelters in the city of Popayán. The results of the research were analyzed in an SPSS statistical package, by means of a descriptive statistic, correlating sex, age and race, being considered significant when the level is <0.01 by pearson correlation. We sampled 27 animals with scabies lesions, which is divided into 15 animals from the fundación para la protección de los animales vida animal (FPPAVA) in which 100% (n=15) of the sampled population came out negative and 12 animals from the Fundación esperanza vida animal (FEVA) from which approximately 11% (n=3) of the population came out positive sarcoptic mange and 11% (n=3) positive for demodectic mange.